Les proces d'assurance cubains et les Statuts du Fonds. (Pamphlet Series, 1966)
This paper discusses the Cuban insurance cases. The litigation in U.S. courts in which claims have been made under life insurance policies issued by U.S. or Canadian companies to applicants then resident in Cuba is the most extensive body of cases involving Article VIII, Section 2(6) that has come into the courts. The cases suggest that the benefits of Article VIII, Section 2(6), cease to be available to a country once it withdraws from the IMF, even in respect of contracts entered into when the country was a member. This conclusion seems to have been accepted by both courts and counsel in the cases.